Efficacy and safety of enteral supplementation with high-dose vitamin D in critically ill patients with vitamin D deficiency - An-Yi Wang; Yu-Chang Yeh; Kuang-Hua Cheng; Yin-Yi Han; Ching-Tang Chiu; Chai-Chi Chang; I-Ting Wang; Anne Chao (Journal of the Formosan Medical Association)
Background: Vitamin D deficiency is associated with mortality and morbidity in critically ill patients. This study investigated the safety and effectiveness of enteral high-dose vitamin D supplementation in intensive care unit (ICU) patients in Asia. Methods: This was a multicenter, prospective, randomized-controlled study. Eligible participants with vitamin D deficiency were randomly assigned to the control or vitamin D supplementation group. In the vitamin D supplementation group, the patients received 569,600 IU vitamin D. The primary outcome was the serum 25(OH)D level on day 7. Results: 41 and 20 patients were included in the vitamin D supplementation and control groups, respectively. On day 7, the serum 25(OH)D level was significantly higher in the vitamin D supplementation group compared to the control group (28.5 [IQR: 20.2–52.6] ng/mL and 13.9 [IQR: 11.6–18.8] ng/mL, p < 0.001). Only 41.5% of the patients achieved serum 25(OH)D levels higher than 30 ng/mL in the supplementation group. This increased level was sustained in the supplementation group on both day 14 and day 28. There were no significant adverse effects noted in the supplementation group. Patients who reached a serum 25(OH)D level of >30 ng/mL on day 7 had a significantly lower 30-day mortality rate than did those who did not (5.9% vs 37.5%, p < 0.05). Conclusions: In our study, less than half of the patients reached adequate vitamin D levels after the enteral administration of high-dose vitamin D. A reduction in 30-day mortality was noted in the patients who achieved adequate vitamin D levels. Trial registration clinicaltrials.gov id: NCT04292873, Registered, March 1, 2020.